Review on the potential to circulate wood-based materials in the building sector - Sironen Susanna; Iliescu Oana; Niknafs Pardis; Amiri Ali; Rohdin Patrik (Environmental Research: Infrastructure and Sustainability)
The construction industry is considered a resource-intensive industry. Buildings and infrastructure account for half of all extracted materials, almost half of the final energy consumption, as well as about one-third of greenhouse gas emissions and waste flows at the European Union level and worldwide. Therefore, it is necessary to move towards a circular model of material use. This study focuses on wood as one of the key resources with numerous reuse and recycling opportunities along its value chain. The aim of the study is to analyse existing literature and determine the reuse opportunities for recycled wood-based materials from the construction sector. In this literature review, we analysed 137 academic articles published between 2010 and 2023 on the potential to recycle and reuse wood-based materials in the construction industry, the environmental and economic benefits, as well as drivers and barriers of this model. Firstly, the results show a growth of papers with a more holistic perspective on the subject throughout the studied period, indicating a growing emphasis on resource efficiency and circular practices. Secondly, results also indicate the gradual change in the recycling and reuse of wood-based materials practices over time, from energy generation to more value-adding and long-lasting products. However, the literature lacks more precise information on the targeted reuse of recycled materials and the economic benefits, indicating that further research is needed in this area.